Measurement of optical properties of pig esophagus by using a modified spectrometer set‐up. Issue 1 (2nd May 2017) - Hohmann, Martin; Lengenfelder, B.; Kanawade, R.; Klämpfl, F.; Douplik, A.; Albrecht, H.
Abstract: Optical properties ( μa, μs and g) of certain human tissue types such as skin and blood have been very well investigated. However until today, for internal body organs such as the esophagus they are not well characterized. For ex‐vivo measurements "Inverse Adding Doubling" (IAD) and Inverse Monte‐Carlo‐Simulation (IMCS) are state of the art. Both methods need the measurement of the collimated transmission. Current methods lack a proper way of measuring the collimated transmission. Hence, this measurement of the g‐factor has a systematic error. Therefore, for the measurement of the collimated transmission, a new approach has been developed and evaluated with intralipid. Finally, the optical properties of mucosa, sub mucosa, muscularis and adventitia of pig esophagus tissue are calculated with IAD. The results are promising and in agreement with published literature. Abstract : Optical properties ( μa, μs and g) of certain human tissue types such as skin and blood have been very well investigated. However until today, for internal body organs such as the esophagus they are not well characterized. For ex‐vivo measurements "Inverse Adding Doubling" (IAD) and Inverse Monte‐Carlo‐Simulation (IMCS) are state of the art. Both methods need the measurement of the collimated transmission. For this measurement of the g‐factor a new approach has been developed and evaluated with intralipid.